Acute endocrinology : from cause to consequence - Alves, Mikael (Humana Press, 2008)
Until recently, endocrinology and critical care medicine were two specialties in medicine that were rather uncomfortable with each other and hence quite i- lated. Fortunately, these two 'alien' disciplines have joined forces in successful attempts to perform high quality research in order to clarify the unknown. By integrating endocrinology in critical care medicine, or vice-versa depending on the specialty of the observer, new experimental and clinical data on the complex endocrine and metabolic derangements accompanying non-endocrine severe i- nesses came available which generated important novel insights with relevant clinical implications. In addition, the state of the art diagnosis and management of primary endocrine diseases that represent life-threatening situations leading to ICU admission has been updated. This issue of Contemporary Endocrinology aims at compiling the new ?ndings. The book indeed covers both areas of 'Acute Endocrinology' that are often taking care of at very distant sites within hospitals. The ?rst part deals with the classical life-threatening illnesses caused by primary endocrine diseases such as thyrotoxicosis, hypothyroidism, acute adrenal crisis, acute calcium disorders, pheochromocytoma, severe hyper- and hypoglycemia . The second part looks at endocrinology from the ICU side, starting with a g- eral overview of the dynamic neuroendocrine and metabolic stress responses in the condition of intensive care-dependent, non-endocrine critical illness.